ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN DI KANTOR KECAMATAN LANDASAN ULIN - Dwi Prihatiningrum Sulistyani (JURNAL KINDAI, 2017)
Abstract: The purpose of this study was to analyze the satisfaction levels towards the services of Landasan Ulin Subdistrict Office. The research method was quailtative analysis. The samples amount 100 people. The results of this research showed that the poor services quality may cause people’s disatisfaction. The entire services of Landasan Ulin Subdistrict Office provided valued as